Overview of drugs approved by the FDA in 2022 - D. V. Kurkin; E. I. Morkovin; D. A. Bakulin; Yu. V. Gorbunova; Yu. A. Kolosov; M. A. Dzhavakhyan; I. E. Makarenko; R. V. Drai; A. V. Zaborovsky; O. V. Shatalova; A. V. Strygin; V. I. Petrov; et al. (Фармация и фармакология (Пятигорск))
The aim of the work is to conduct a review of medications approved by the FDA in 2022.Materials and methods. In searching for the materials to write this review article, bibliographic databases including PubMed, Google Scholar and e-library.ru were utilized. The search was conducted for the publications spanning the period from 2008 to 2023. Herewith, the following keywords and word combinations were used: new drug approval, NDA, drug authorization, approval package, breakthrough medicine.Results. The discovery and development of medications are among the most crucial scientific processes in healthcare. Developing a new drug is a highly intricate, expensive, and time-consuming process. Nowadays, the problem of costs reduction and the process of expedited discovering of new medications are particularly pertinent. To optimize the search for active compounds, virtual and high-throughput screenings, machine learning, artificial intelligence, cryo-electron microscopy, and drug repurposing are employed. Simultaneously, the search for original molecules to serve as the basis for innovative drugs continues. This article presents a review of medications approved by the FDA in 2022 for the treatment of various pathologies.Conclusion. A drug development is a complex and resource-intensive process, with only a small fraction of candidates advancing to clinical trials. A drug design evolves in tandem with societal needs, and this review highlights some of the medications approved by the FDA in 2022. Technological advancements are expected to expedite drug development, potentially reducing the time to the market. Biotechnology, including cell therapy, holds significant prospects, and achievements in genetic mapping and chip technologies will enhance the accessibility of personalized pharmacology.